2018
DOI: 10.1016/j.fct.2018.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effect of salidroside and curcumin on the immunoreactivity of rats subjected to a chronic mild stress model

Abstract: Deregulated cytokines' production is found in depressed patients. Salidroside and curcumin both have been described with potential antidepressant-like activities. The present study investigated the effect of pure salidroside, curcumin and their combination on the immunoreactivity of animals, subjected to a chronic mild stress (CMS) model, followed by lipopolysaccharide (LPS)-induced inflammation. Wistar male rats were separated in the following six groups: control, CMS model, fluoxetine (2.5 mg/kg, oral), sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Rhodiola rosea L. (known also as Sedum rosea (L.) Scop., Golden Root, Arctic Root, Roseroot), is the most popular medicinal plant among the 200 species of family Crassulaceae, 4,5 possessing important biological activities, such as: adaptogenic and stress protective, anti‐depressive, anti‐tumour, anti‐inflammatory, neuroprotective, cardioprotective, hepatoprotective, immunostimulating and immunomodulating activities, 6–8 demonstrated in numerous in vitro and in vivo studies 9–11 . The principal raw material used for the production of R. rosea supplements are the rhizomes, and some of the most popular preparations, such as Arctic Root® (based on the standardised SHR‐5 extract), 11 Vitano® (WS® 1375 extract), 12 ADAPT‐232 forte® (fixed combination of R. rosea , Eleutherococcus senticocus and Schisandra chinensis extracts), 13 are registered as herbal medicines in Europe 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Rhodiola rosea L. (known also as Sedum rosea (L.) Scop., Golden Root, Arctic Root, Roseroot), is the most popular medicinal plant among the 200 species of family Crassulaceae, 4,5 possessing important biological activities, such as: adaptogenic and stress protective, anti‐depressive, anti‐tumour, anti‐inflammatory, neuroprotective, cardioprotective, hepatoprotective, immunostimulating and immunomodulating activities, 6–8 demonstrated in numerous in vitro and in vivo studies 9–11 . The principal raw material used for the production of R. rosea supplements are the rhizomes, and some of the most popular preparations, such as Arctic Root® (based on the standardised SHR‐5 extract), 11 Vitano® (WS® 1375 extract), 12 ADAPT‐232 forte® (fixed combination of R. rosea , Eleutherococcus senticocus and Schisandra chinensis extracts), 13 are registered as herbal medicines in Europe 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These psychoactive drugs exert their effect in part through the reduction of the production of pro-inflammatory cytokines such us interleukin-1 β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) [40,42], therefore, modulating immune responses. Interestingly, natural compounds such as curcumin and salidroside have shown antidepressant effect in stress-induced depression with reported decreased inflammatory IL-6 and TNF-α signals (42,43], driving to immune regulation. A similar response was observed in patients suffering from other pathologies under Ocoxin regimen, reporting immunoregulatory properties and reducing TNF-α level [25].…”
Section: Ocoxin and Depressionmentioning
confidence: 99%
“…Plant adaptogens alleviate the negative effects on health from prolonged exposure to stress, and this is at least in part a result of immunomodulation. Our previous studies found that treatment of stressed rats with extracts from Rhodiola rosea L. and Curcuma longa L. as well as their respective marker substances, salidroside and curcumin, attenuate the production of both IL-6 and TNF-α levels in brain tissue and in serum (Vasileva et al, 2017(Vasileva et al, , 2018. Salidroside has been previously reported to inhibit the pro-inflammatory cytokines' production in depression models (Yang et al, 2014;Zhu et al, 2015).…”
mentioning
confidence: 99%
“…colorectal carcinoma) and other diseases (Salehi et al, 2019). In recent years, extensive studies revealed the profound activity of curcumin on depressive and stress-induced disorders, especially regarding the accompanying immune-inflammatory dysregulations, both in experimental and clinical settings (Jiang et al, 2013;Kaufmann et al, 2016;Lopresti et al, 2014;Vasileva et al, 2018). However, despite the diverse range of beneficial activities designated to this natural compounds there are also some controversies about its mechanisms of action.…”
mentioning
confidence: 99%